2015
DOI: 10.3389/fphys.2015.00177
|View full text |Cite
|
Sign up to set email alerts
|

Inherited macular degeneration-associated mutations in CNGB3 increase the ligand sensitivity and spontaneous open probability of cone cyclic nucleotide-gated channels

Abstract: Cyclic nucleotide gated (CNG) channels are a critical component of the visual transduction cascade in the vertebrate retina. Mutations in the genes encoding these channels have been associated with a spectrum of inherited retinal disorders. To gain insight into their pathophysiological mechanisms, we have investigated the functional consequences of several CNGB3 mutations, previously associated with macular degeneration (Y469D and L595F) or complete achromatopsia (S156F, P309L, and G558C), by expressing these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Folding, intracellular processing, and transport are thought to be impaired [29]. The effects of individual CNGA3 amino acid substitutions on CNG channel function have mainly been studied in vitro [21,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. Some insights have been gained, but the exact mechanisms linking CNGA3 amino acid substitutions to cone photoreceptor dysfunction and eventual degeneration are still not well understood.…”
Section: The Mutation Landscape In Cnga3and Cngb3-linked Achromatopsiamentioning
confidence: 99%
“…Folding, intracellular processing, and transport are thought to be impaired [29]. The effects of individual CNGA3 amino acid substitutions on CNG channel function have mainly been studied in vitro [21,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. Some insights have been gained, but the exact mechanisms linking CNGA3 amino acid substitutions to cone photoreceptor dysfunction and eventual degeneration are still not well understood.…”
Section: The Mutation Landscape In Cnga3and Cngb3-linked Achromatopsiamentioning
confidence: 99%
“…AMD is a progressive blinding disease with no cure and is the main cause of visual disability in industrialized countries [10][11][12]. Increasing evidence has shown that mitochondrial and RPE cells damage plays important roles in the pathogenesis of AMD [13].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, functional studies are needed to validate the possible pathogenic effect of the respective variants. Commonly used methods to characterize the functionality of mutant CNG channels involve calcium imaging and patch‐clamp recordings of heterologously expressed mutant channels (Burkard et al, 2018; Dai & Varnum, 2013; Koeppen et al, 2008, 2010; Kuniyoshi et al, 2016; Liu & Varnum, 2005; Matveev et al, 2010; Meighan et al, 2015; Muraki‐Oda et al, 2007; Patel et al, 2005; Reuter et al, 2008; Shaikh et al, 2015; Täger et al, 2018; Tränkner et al, 2004). Furthermore, a recently developed functional assay proposes a fluorescence‐based, high‐throughput calcium influx‐based approach for analyzing mutant CNGA3 channels (Jacobson et al, 2019).…”
Section: Overview Of Cnga3 Variants Underlying Achmmentioning
confidence: 99%
“…Following functional characterization of heterologously expressed mutant channels in previously conducted studies, 27 out of 54 missense variants completely abolished formation of functional channels (Koeppen et al, 2008, 2010; Liu & Varnum, 2005; Matveev et al, 2010; Muraki‐Oda et al, 2007; Patel et al, 2005; Shaikh et al, 2015; Tränkner et al, 2004). Seventeen previously analyzed missense substitutions allowed the formation of functional channels but with impaired/altered functionality such as impaired protein folding and/or channel trafficking or altered biophysical properties, for example, altered apparent cGMP‐sensitivity or ion selectivity (Burkard et al, 2018; Dai & Varnum, 2013; Koeppen et al, 2008; Liu & Varnum, 2005; Meighan et al, 2015; Muraki‐Oda et al, 2007; Patel et al, 2005; Reuter et al, 2008; Tränkner et al, 2004). Furthermore, an improvement in the mutant channel functionality was achieved in a total of ten missense variants by using chemical chaperones or co‐expressing the CNGB3 subunit and/or reducing the cell cultivation temperature from the standard 37°C to 27/28°C, a procedure that is known to enhance protein folding and trafficking (Koeppen et al, 2010; Kuniyoshi et al, 2016; Patel et al, 2005; Reuter et al, 2008).…”
Section: Overview Of Cnga3 Variants Underlying Achmmentioning
confidence: 99%
See 1 more Smart Citation